Rancang Bangun Sistem Informasi Pelayanan Publik Berbasis Web Menggunakan Metode Extreme Programming di Desa Bhuana Giri - Ardiantara, I Nyoman Ngurah; Yudi, I Nyoman Yudi Anggara Wijaya; Putra, Anak Agung Gede Adi Mega (Sekolah Tinggi Ilmu Komputer PGRI Banyuwangi, 2025)
Development of a web-based public service information system in Bhuana Giri Village, Bebandem District, Karangasem Regency, Bali. This village, with a population of 7,579 people, currently still uses a manual system for administrative services, which includes making various certificates. This manual system is considered less efficient and is at risk of data corruption or loss. To overcome this problem, a web-based system is proposed using the extreme programming method. The research aims to improve the efficiency of public services, speed up the process of making letters, and facilitate access to information for the community. The system is expected to enable online letter submission and more effective information search, in line with the development of information technology that has penetrated various aspects of people's lives.